Morphologie and hydrodynamic impact of a period of high energy in the intertidal section of an embayed beach and in three mesotidal semi-sheltered pocket beaches: Example of the Xynthia storm in the Rhuys peninsula (France) - Dubois, A. (Johann Heinrich of Thuenen Institute Bundesforschungsanstalt Fuer Landwirtschaft Braunschweig Voelkenrode, 2014)
From experimental topographic and hydrodynamic data, this paper highlights the principal morphological and volumetric variations in four semi-sheltered closely spaced pocket beaches along the southern shoreface of Rhuys Peninsula (South Britanny, France), during a period of high energy, culminating in Storm Xynthia. These four beaches are subjected to a mixed hydrodynamic regime, with a mesotidal range. In the western part of Rhuys Peninsula, three beaches adjacent to each other are oriented north-west/south-east while in the eastern part, an embayed beach, larger in size, exhibits a more variable shoreline geometry and is more exposed to an oceanic wave climate. Along this latter beach, during the storm, three currentmeters comprising wave gauges were deployed (at the two ends and in the centre of the bay) in the lower intertidal area. Results show that tidal currents are more forced in direction than in intensity and an important storm surge is measured (05-0.63 m). This leads to significant overwash or erosion of the foredune depending on its morphology. Topographic surveys, carried out within 24 hours, highlight a substantial erosion rate exceeding 55 of the initial sediment budget. During this period of high energy culminating in the storm, the embayed beach profiles underwent a total loss up to 10 of their sediment budget. On the contrary, the three western pocket beaches accreted to about +2 of their initial sediment budget. It clearly appears that such an energetic event does not lead to a widespread erosion of all the beaches of Rhuys Peninsula. The intertidal morphology and the local subtidal morphobathymetric context govern the sedimentary exchanges, promoting storage or by-pass of sediment between these two sections in topographic incisions. Thus, along this shoreface, each sandy system adopts a single mor-phodynamic signature in response to an energetic event.